Estimation of geomagnetic field disturbance using the wavelet transform - Mandrikova, O. V.; Solovjev, I. S.; Khomutov, S. Yu; Baishev, D. G.; Geppener, V. V.; Klionskiy, D. M. (Pattern recognition and image analysis, 2016)
This paper discusses the main aspects of geomagnetic data processing using the wavelet transform. The wavelet transform is shown to be efficient for automatic extraction of unperturbed level of the horizontal component of the Earth’s magnetic field. As a result, it becomes possible to significantly reduce the errors arising during automatic calculations of the local geomagnetic activity index (local K-index) in comparison with adaptive smoothing (KAsm is Adaptative Smoothing method) recommended by INTERMAGNET. It has been found that prior to magnetic storms, we can observe a weak rise of geomagnetic activity in different frequency bands connected with the development of an approaching storm.